The murders in Great Diddling : a novel - Bivald, Katarina, 1983- (Poisoned Pen Press, 2024)
"The best stories are the ones we didn't know needed to be told The small, rundown village of Great Diddling is full of stories--author Berit Gardner can feel it. The way the villagers avoid outsiders, the furtive stares and whispers in the presence of newcomers... Berit can sense the edge of a story waiting to be unraveled, and she's just the person to do it. In fact, with a book deadline looming over her and no manuscript (not even the idea for a manuscript, truth be told), Berit doesn't just want this story. She needs it. Then, while attending a village tea party, Berit becomes part of the action herself. An explosion in the library of the village's grand manor kills a local man, and the resulting investigation and influx of outsiders sends the quiet, rundown community into chaos. The residents of Great Diddling, each one more eccentric and interesting than any character Berit could have invented, rewrite their own narrative and transform the death of one of their own from a tragedy into a new beginning. Taking advantage of Great Diddling's new notoriety, the villagers band together to start a book and murder festival designed to bring desperately-needed tourists to their town. What they couldn't have predicted is how the new story they've begun to tell will change all their lives forever. Uplifting, charming, and laugh-out-loud funny, The Murders in Great Diddling by New York Times bestselling author Katarina Bivald is a celebration of the life-changing magic of books and the people who love them"--